(untitled) (International Seven Journal of Multidisciplinary, 2024)
This study explores the key socio-technological aspects of the 25-year electrification process using photovoltaic solar technology in the rural community of Santa María del Loreto, emphasizing its crucial relationship with beneficiaries. Participation, training, and adherence to resource usage guidelines are identified as primary variables facilitating the assimilation of this technology, prompting users to collectively modify energy consumption habits and customs. These efforts have effectively promoted local capacity building for community adoption of photovoltaic technology as a replacement for diesel generators in the electrification process.